1999
DOI: 10.1046/j.1365-2249.1999.00878.x
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-gamma (IFN-γ)- and tumour necrosis factor (TNF)-induced nitric oxide as toxic effector molecule in chronic dextran sulphate sodium (DSS)-induced colitis in mice

Abstract: Excess nitric oxide formation caused by the activity of the inducible nitric oxide synthase has been implicated as a toxic effector molecule in the pathogenesis of experimental colitis and inflammatory bowel disease. It was therefore investigated whether inhibition of this synthase or the cytokines TNF and IFN-gamma, inducers of nitric oxide synthase, had effects on chronic colitis in mice. Chronic colitis was induced in mice by repeated feeding of DSS. Cytokines were neutralized by treatment with MoAbs and ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
242
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(255 citation statements)
references
References 73 publications
12
242
1
Order By: Relevance
“…In both patients and animal models of IBD, a positive correlation between the overproduction of pro-inflammatory cytokines (e.g., IL-1b, TNF-α, IFN-γ) and an overexpression of iNOS was found. This expression was primarily detected in the lamina propria mononuclear cells and the colon epithelial cells of the inflamed mucosa [6,16,17,27,30,71,72] . Several studies conducted on a dextran sulfate sodium (DSS)-induced experimental model of colitis in BALB/c mice indicated that the neutralization of endogenous TNF-α and/or IFN-γ ameliorated the chronic colitis and concomitantly decreased the generation of NO.…”
Section: Cytokine Regulation Of No In Ibdmentioning
confidence: 99%
See 2 more Smart Citations
“…In both patients and animal models of IBD, a positive correlation between the overproduction of pro-inflammatory cytokines (e.g., IL-1b, TNF-α, IFN-γ) and an overexpression of iNOS was found. This expression was primarily detected in the lamina propria mononuclear cells and the colon epithelial cells of the inflamed mucosa [6,16,17,27,30,71,72] . Several studies conducted on a dextran sulfate sodium (DSS)-induced experimental model of colitis in BALB/c mice indicated that the neutralization of endogenous TNF-α and/or IFN-γ ameliorated the chronic colitis and concomitantly decreased the generation of NO.…”
Section: Cytokine Regulation Of No In Ibdmentioning
confidence: 99%
“…This observation suggests a possible use of serum NO levels for monitoring disease activity in both types of IBD [16,28,29] . While several studies conducted using animal models indicate the deleterious effect of NO, recent studies have shown that NO may also exert a protective effect against colitis [29][30][31][32] . One study conducted using a DSSinduced colitis model found that nitrite administration exerts both preventive and therapeutic effects in colonic inflammation [33] .…”
Section: No and Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…Sections were analysed for damage to the epithelium including damage to crypts, submucosal oedema, haemorrhage, and infiltration by immune cells. The histology score for each mouse was calculated as the sum of 'Infiltration' and 'Damage of Epithelium' sub-scores, as previously described (18).…”
Section: Histologymentioning
confidence: 99%
“…The distal third of the colon was removed and used for histological analysis as described before [60,63]. Three sections were evaluated obtained each at a 100-lm distance.…”
Section: Assessment Of Histological Scorementioning
confidence: 99%